دراسة الكفاءة الاقتصادية لزراعة أزهار القطف ( القرنفل ) في الساحل السوري - درويش, نضال (Latakia University Journal -Biological Sciences Series, 2019)
نظراً للأهمية الاقتصادية الكبيرة لأزهار القطف ( القرنفل), بوصفها إحدى أهم الزراعات البديلة التي دخلت إلى سوريا حديثاً, ركزنا في هذا البحث على المزايا الاقتصادية, والعوائد المادية الناتجة عن زراعة القرنفل في الساحل السوري, من خلال دراسة التكاليف الإنتاجية, ومؤشرات الكفاءة الاقتصادية بالاستناد إلى بيانات ومعطيات تم جمعها من موقعي البحث( الشامية, الخراب ), معتمدين في تحديد كلفة المواد و الأجور أسعار السوق السائدة, وقد سعينا في هذا البحث لتحقيق الأهداف الآتية: - دراسة واقع تطور زراعة نباتات الزينة في سوريا بشكل عام و الساحل السوري بشكل خاص خلال الفترة 2001 – 2007 م. - حساب التكاليف الإنتاجية لزراعة أزهار القطف ( القرنفل ) في الساحل السوري. - إجراء التقويم الاقتصادي لزراعة أزهار القطف ( القرنفل ) في الساحل السوري. وبنتيجة الدراسة توصلنا إلى النتائج الآتية: * بلغ صافي الربح السنوي المحقق من البيت البلاستيكي الواحد من القرنفل 197974.34 ل.س. * بلغ معامل الربحية بالقياس إلى رأس المال المستثمر 31.22 %, وبالقياس إلى التكاليف الإنتاجية 90 %. * بلغ مؤشر زمن استعادة رأس المال للقرنفل 3.20 سنة. Due to the high economical importance of Cut Flowers (Carnation/Dianthus Caryophyllus) as one of the most significant alternative plantations introduced to Syria recently, this research has concentrated on the economical properties and the profits resulting from Carnation plantation on the Syrian Coast through studying the productivity cost and the indicatives of economical feasibility based on data and statements gathered from the two sites of research (Shamieh and Khrab), and relying, in determining wages and materials costs, on the current market prices. In this research, we have sought to achieve the following targets: · Studying the development of Ornamental plantation in Syria, in general, and on the Syrian Coast, in particular, during the period from 2001 to 2007. · Calculating the productivity cost of Cut Flowers (Carnation /Dianthus Caryophyllus ) on the Syrian Coast. · Making an economical evaluation of the Cut Flowers (Carnation/Dianthus Caryophyllus) plantation on the Syrian Coast. In conclusion, we have reached the following results: · Totally achieved net profit per annum from one greenhouse of Carnation plantation amounted to 197974.34 Syrian Pounds. · Profitability Coefficient in proportion to the invested capital has amounted to 31.22% and to 90% in proportion to the productivity cost. · Time indicator of Capital recovery for (Carnation/Dianthus Caryophyllus) has amounted to 3.20 years.